School English, literature and the knowledge-base question. Issue 1 (2nd January 2019) - Yates, Lyn; Davies, Larissa McLean; Buzacott, Lucy; Doecke, Brenton; Mead, Philip; Sawyer, Wayne
Abstract: This article takes up questions about knowledge and the school curriculum with respect to literary studies within subject English. Its intention is to focus on literary studies in English from the context of current waves of curriculum reform, rather than as part of the conversations primarily within the field of English, to raise questions about the knowledge agenda, and the knowledge-base agenda for teaching and teacher education. The selection of texts and form of study of literature within the English curriculum has long been an area of controversy. Without assuming a particular position on knowledge in this area, this article shows that important questions of what knowledge-base teachers are expected to bring to their work are elided both in current regulations and debates, and in research on 'good teaching' in this area. If 'literary studies' (as a discipline or university major) is itself an unstable and changing field, what kind of knowledge does a good English teacher bring to their work? This paper takes up these questions in the context of the Australian Curriculum and standards for teacher registration, but it also points to the way these issues about knowledge are of broader relevance for researchers and teacher education.